Analisis dan Desain Sistem Produksi Mi Aceh Spesial Menggunakan Model Process-Oriented Analysis - Rahmat Fadhil; Tajuddin Bantacut; . Machfud (Institut Pertanian Bogor, 2018)
This study describes the analysis and design of production systems at an Aceh noodle restaurant based on the approach of process-oriented analysis (POA). POA is a technique that can be used to design or re-engineering a production system. This system useD a type of static analysis with two models i.e., value flow diagram (VFD) and resource flow diagrams (RFD). The results showed that the POA method is very useful to study the analysis and design of production systems. Application of this method of learning and project engineering production provides an enormous benefit in analyzing and designing the production system of special Aceh noodles at a restaurant, which includes the amount of information, numbers, and economic return value (VFD), as well as information on the flow of resources (including mass, energy, and embodied energy) and their respective ecological values (RFD).